Case report: 10-year survival of a patient with a primary hepatic gastrointestinal stromal tumor - Lian, Jie; Feng, Meiyan; Zhang, Shumei; Lu, Haibo (Frontiers in Oncology, 2022)
Background Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors of the gastrointestinal tract. Extra-gastrointestinal stromal tumors (EGISTs) predominantly arise outside the gastrointestinal tract, although primary hepatic GISTs are extremely rare. GISTs are highly aggressive; they often grow to a large size. Here, we report the 10-year survival of a patient with a primary hepatic GIST following sequential response therapy. Case presentation A 50-year-old Chinese man complained of fatigue and slight abdominal pain, and presented with a large lump in the liver, which was detected by computed tomography (CT). He was subsequently diagnosed with a primary hepatic GIST, based on CT-guided fine needle aspiration cytology and immunohistochemistry analyses. The presence of GIST or EGIST metastases was excluded using CT, esophagogastroduodenoscopy, colonoscopy, and ultrasound. Cytological examination showed that the tumor was composed of epithelioid and spindle cells. Immunohistochemistry analysis revealed positive staining for CD117 (KIT) and DOG1, and negative staining for CD34, S-100, and α-smooth muscle actin (SMA). Following tumor ablation with argon-helium cryosurgery, the patient received imatinib mesylate for 61 months. However, this treatment was discontinued because of disease progression, at which point interventional therapy was administered once. One month later, sunitinib malate was administered for 71 months. The patient achieved long-term survival for 135 months. Conclusions EGISTs can be easily misdiagnosed as other types of tumors because they have no specific characteristics to distinguish them during imaging examinations. However, our case study demonstrates that the long-term survival of patients with EGISTs can be achieved with molecular targeted therapy.